2017
DOI: 10.1038/cr.2017.112
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of histone H2A and histone variant H2A.Z-interacting proteins by bPPI-seq

Abstract: H2A is a nucleosome core subunit involved in organizing DNA into a chromatin structure that is often inaccessible to regulatory enzymes. Replacement of H2A by its variant H2A.Z renders chromatin accessible at enhancers and promoters. However, it remains unclear how H2A.Z functions so differently from canonical H2A. Here we report the genome-wide identification of proteins that directly interact with H2A and H2A.Z in vivo using a novel strategy, bPPI-seq. We show that bPPI-seq is a sensitive and robust techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In yeast, mutations in H2A.Z increase dependence on the SWI2/SNF2 complex for transcriptional activation of several genes, implying that the histone variant and chromatin remodeler have cooperative functions (Santisteban et al, 2000). Furthermore, in mammals, SWI2/SNF2 subunits interact with H2A.Z, although the implications of this interaction have not been explored (Goldman et al, 2010;Li et al, 2012;Zhang et al, 2017b). While the SWR1 CRC and the SWI2/ SNF2 complex have parallel roles in development and environmental responses in plants, there is a dearth of studies that focus on the direct intersection of these two complexes in chromatin and transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, mutations in H2A.Z increase dependence on the SWI2/SNF2 complex for transcriptional activation of several genes, implying that the histone variant and chromatin remodeler have cooperative functions (Santisteban et al, 2000). Furthermore, in mammals, SWI2/SNF2 subunits interact with H2A.Z, although the implications of this interaction have not been explored (Goldman et al, 2010;Li et al, 2012;Zhang et al, 2017b). While the SWR1 CRC and the SWI2/ SNF2 complex have parallel roles in development and environmental responses in plants, there is a dearth of studies that focus on the direct intersection of these two complexes in chromatin and transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, mutations in H2A.Z increase dependence on the SWI2/SNF2 complex for transcriptional activation of several genes, implying that the histone variant and chromatin remodeler have cooperative functions (Santisteban et al, 2000). Furthermore, in mammals, SWI2/SNF2 subunits interact with H2A.Z, although the implications of this interaction have not been explored Zhang et al, 2017b). While the SWR1 CRC and the SWI2/SNF2 complex have parallel roles in development and environmental responses in plants, there is a dearth of studies that focus on the direct intersection of these two complexes in chromatin and transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although antibody mediated protein isolation couple with mass spectrometry approach has been a standard method to identify TF interacting partners and characterize their functional molecular complexes, it becomes urge to develop a robust method to functional characterize how these transcription factors act during biological process in the post-human genome project era. Here, Dr. Zhao and his colleagues in the National Heart, Lung, and Blood Institute of NIH develop a sensitive and robust strategy to globally identify and characterize in vivo protein–protein interactions termed bait protein–protein interaction-sequencing (bPPI-seq) (Zhang et al in Cell Res doi:10.1038/cr.2017.112, 2017 ). As a proof-of-principle, they demonstrated that genome-wide interacting partners of histone variant H2A.Z are mainly involved in transcriptional regulation which is distinct from the interacting proteins of canonical histone H2A.…”
mentioning
confidence: 99%
“…Recently, a team of researchers led by Dr. Keji Zhao of the National Heart, Lung, and Blood Institute, National Institute of Health, has developed a novel strategy to identify protein interacting partners in a genome-wide scale [ 1 ]. The method termed bait protein–protein interaction-sequencing (bPPI-seq) takes advantage of the fact that active green fluorescent protein (GFP) can be reconstituted and emit fluorescent light from two half GFP moieties when they are brought to a close proximity through protein–protein interaction [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation